Clove oil additives in vegetable oil: an assessment of fuel properties - Gamayel, Adhes (Jurnal Polimesin, 2024)
Vegetable oil, obtained from plants such as coconut or Jatropha curcas, serves as a valuable renewable energy source. Nonetheless, it presents certain limitations in comparison to diesel fuels, namely, low volatility and high viscosity. One straightforward approach to overcome these limitations is the addition of high-volatility oil and low-viscosity oil. In this study, we incorporated 10% clove oil into coconut oil and Jatropha curcas oil. Fuel properties, including density, viscosity, flash point, and heating value, were measured in accordance with international standards. Additionally, Thermogravimetric Analysis (TGA) testing was performed to detect decomposition during the heating process. The findings indicated that the addition of clove oil increases density (from 0.922 g/ml to 0.934 g/ml), while other properties decrease, such as viscosity (from 30.12 cst to 27.7 cst), flash point (from 286°C to 182°C), and heating value (from 37.1 MJ/kg to 35.8 MJ/kg). TGA demonstrated that the inclusion of clove oil resulted in increased decomposition within the temperature range of 200°C–400°C, suggesting that clove oil falls into the category of medium-volatile oils. Although the addition of clove oil were able to modify the fuel properties of vegetable oil, it did not align with the characteristics of conventional diesel fuel and necessitates further modification for practical implementation